2012
DOI: 10.1103/physrevstab.15.123501
|View full text |Cite
|
Sign up to set email alerts
|

Charge stripping ofU238ion beam by helium gas stripper

Abstract: Development of a nondestructive, efficient electric-charge-stripping method is a key requirement for next-generation high-intensity heavy-ion accelerators such as the RIKEN Radioactive-Isotope Beam Factory. A charge stripper employing a low-Z gas is an important candidate applicable to high-intensity uranium beams for replacing carbon-foil strippers. In this study, a high-beam-transmission chargestripping system employing helium gas for 238 U beams injected at 10:8 MeV=u was developed and demonstrated for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…11(a). It is known as the shell effect, first observed by Moak et al [45], and also observed in the case of uranium stripping [34]. This discrepancy is caused by the difficulty of ionizing from the L shell of the Kr ion.…”
Section: A Charge State Distributionmentioning
confidence: 93%
See 3 more Smart Citations
“…11(a). It is known as the shell effect, first observed by Moak et al [45], and also observed in the case of uranium stripping [34]. This discrepancy is caused by the difficulty of ionizing from the L shell of the Kr ion.…”
Section: A Charge State Distributionmentioning
confidence: 93%
“…We constructed a prototype of a windowless gas charge stripping system in a beam line based on the basic design of the differential pumping system [34,39,40]. Figures 3 and 4 show the overview of the beam line and its detailed diagram, respectively.…”
Section: Gas Charge Stripping Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides basic research, the investigation of these processes is also motivated by their paramount importance for many applications, such as ion stripping and beam transport in accelerators and storage rings [1][2][3] as well as ion-driven fusion devices [4][5][6]. Essential here is that interactions between projectile ions and constituents of the residual gas can lead to a change of the projectile charge state.…”
Section: Introductionmentioning
confidence: 99%